Estimation of Sedimentary Transport Induced by North Waves in the Southern Portion of the West Shore of the Canal of Access to the Port of Rio Grande (4ª Secção da Barra do Rio Grande, RS) - Lima, Gabriel Mello Vieira (2019)
The study sought to estimate the average sediment transport induced by the waves coming from Lagoa dos Patos, RS. The sedimentological data (average D50 found equal to 0.1618 mm) and bathymetric data were acquired using the SWAN model calibrated by Lemke (2015), all with the objective of feeding the DELFT 3D - morphological module, which is capable of estimating the mean sedimentary transport of the region. The highest values ”‹”‹of mean sediment transport were for the regions nearer to the wave incidence, that is, with the wave incident from North direction, the highest transport value occurred downstream of the TECON quay. In spite of all the limitations of the data of the physical forcing, it was concluded that, in the cases considered, there is a rapid decay in the height of the wave along the channel, being almost imperceptible to its occurrence in the southern part. In the results of the transported volumes in the studied margin, because with the propagation of these cases of waves, there was not sufficient energy to mobilize sediments at the opposite end to the entrance of the waves. Also, it is not possible to consider the rates found as area erosion / accretion, because other important forcing was not included in the model.